2013
DOI: 10.3109/0886022x.2013.819766
|View full text |Cite
|
Sign up to set email alerts
|

Impact of restarting warfarin therapy in renal disease anticoagulated patients with gastrointestinal hemorrhage

Abstract: Background: Atrial fibrillation (AF) is emerging as a major health problem. The prevalence is as high as 32% in patients with renal disease. Gastrointestinal bleeding (GIB) is a frequent complication. Objective: To investigate the hazards of resumption or discontinuation of anticoagulation in renal disease patients after an episode of GIB. Design, settings, participants and measurements: This is a multicenter retrospective cohort of patients with AF on warfarin that developed an episode of GIB. Chronic kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…1,2 Contrary to only gastrointestinal bleeding in the study by Khalid et al, 1 the "bleeding" definition in our study included intracerebral bleeding, gastrointestinal bleeding, intraocular bleeding, hematuria, and unspecified location of bleeding, which could be a possible reason for the difference in bleeding risk between the 2 studies.…”
mentioning
confidence: 47%
See 2 more Smart Citations
“…1,2 Contrary to only gastrointestinal bleeding in the study by Khalid et al, 1 the "bleeding" definition in our study included intracerebral bleeding, gastrointestinal bleeding, intraocular bleeding, hematuria, and unspecified location of bleeding, which could be a possible reason for the difference in bleeding risk between the 2 studies.…”
mentioning
confidence: 47%
“…Qureshi and colleagues also mentioned that they observed a 78% reduction in the risk of mortality in hemodialysis patients with AF who were on warfarin compared with those not on warfarin and mentioned that mortality risk assessment could be important when considering risk-benefit assessment on warfarin use in AF patients undergoing dialysis. 1 Chan and colleagues 4 also conducted a similar study and found that warfarin use was associated with a 27% higher risk of mortality in hemodialysis patients. In our AF cohort, we had access to information on patients' mortality (all-cause mortality).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…In a US cohort, we reported a 72% increase in risk of gastrointestinal bleeding in hemodialysis patients on warfarin compared with hemodialysis patients not on warfarin. 2 However, very rarely did this bleeding lead to a fatality. We believe that the reason for the lower incidence of bleeding compared with that in our study is that Shah et al analyzed peritoneal dialysis and hemodialysis patient collectively.…”
Section: To the Editormentioning
confidence: 99%
“…Moreover, in our analysis, we noticed a 78% reduction in mortality risk among dialysis patients on warfarin compared with dialysis patients not on warfarin. 2 This is an important consideration because mortality is an important outcome to consider in these patients when risk-benefit decisions are being made. This beneficial effect of warfarin to prevent cardiovascular mortality is almost similar to that of aspirin, as noted in many previous trials.…”
Section: To the Editormentioning
confidence: 99%